2019
DOI: 10.1080/17429145.2019.1680752
|View full text |Cite
|
Sign up to set email alerts
|

Growth-promoting bacteria alleviates drought stress of G. uralensis through improving photosynthesis characteristics and water status

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Growth-promoting bacteria alleviates drought stress of G. uralensis through improving photosynthesis characteristics and water status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 63 publications
(68 reference statements)
5
23
0
4
Order By: Relevance
“…Drought leads to a decrease in both photosynthetic pigment content and photosynthetic efficiency of plants resulting from decreased leaf area, plant height, biomass accumulation, and yield formation. The content of the main photosynthetic pigments chlorophylls (Chl) and carotenoids (Car), while indirect, is the most important biochemical indicator of plant photosynthetic activity [ 42 , 43 , 44 ]. Many studies have shown that bacterial inoculation may positively influence the maintenance of photosynthetic pigments in plants accompanied by improved drought tolerance [ 42 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought leads to a decrease in both photosynthetic pigment content and photosynthetic efficiency of plants resulting from decreased leaf area, plant height, biomass accumulation, and yield formation. The content of the main photosynthetic pigments chlorophylls (Chl) and carotenoids (Car), while indirect, is the most important biochemical indicator of plant photosynthetic activity [ 42 , 43 , 44 ]. Many studies have shown that bacterial inoculation may positively influence the maintenance of photosynthetic pigments in plants accompanied by improved drought tolerance [ 42 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The content of the main photosynthetic pigments chlorophylls (Chl) and carotenoids (Car), while indirect, is the most important biochemical indicator of plant photosynthetic activity [ 42 , 43 , 44 ]. Many studies have shown that bacterial inoculation may positively influence the maintenance of photosynthetic pigments in plants accompanied by improved drought tolerance [ 42 , 45 , 46 ]. B. pumilus alleviated drought-induced damage to the photosynthetic activity of Glycyrrhiza uralensis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPR also increase the absorption of the elements involved in the creation of structure of the Chl molecule and result in Chl concentration (Dutta and Khurana 2015;Ngumbi and Kloepper 2016;Parray et al 2016;Ruzzi and Aroca 2015). It is also possible that under stress conditions, the PGPR prevent the destruction of Chl molecules to some extent, through stimulation of genes involved in the protection against photo-oxidative stress (Zhang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Licorice adapts very well to low-fertility soils and drought. In fact, it has been used in the ecological restoration of arid regions [22]. In its natural habitats, the licorice rhizosphere harbors actinobacteria, rhizobia, other soil bacteria, AM, and DSE with plant growth-promoting activity [23,24].…”
Section: Introductionmentioning
confidence: 99%